2006
DOI: 10.1038/nature04894
|View full text |Cite
|
Sign up to set email alerts
|

A soft-bodied mollusc with radula from the Middle Cambrian Burgess Shale

Abstract: Summary:Odontogriphus omalus was originally described as a problematic non-biomineralized lophophorate organism. Here we reinterpret Odontogriphus based on 189 new specimens including numerous exceptionally well-preserved individuals from the Burgess Shale collections of the Royal Ontario Museum. This additional material provides compelling evidence that the feeding apparatus in Odontogriphus is a radula of molluscan architecture comprising two primary bipartite tooth rows attached to a radular membrane and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
98
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(101 citation statements)
references
References 33 publications
(28 reference statements)
3
98
0
Order By: Relevance
“…Some paleontologists and zoologists have argued that these animals are mollusks and therefore are yet another representative of the placophoran grade of organization. Others argue that while they are closely related to mollusks and other lophotrochozoan groups such as annelid worms or perhaps brachiopods, they are not members of the Mollusca (see Vinther and Nielsen 2005;Caron et al 2006;Butterfield 2006 for a sampling of both pro and con arguments).…”
mentioning
confidence: 99%
“…Some paleontologists and zoologists have argued that these animals are mollusks and therefore are yet another representative of the placophoran grade of organization. Others argue that while they are closely related to mollusks and other lophotrochozoan groups such as annelid worms or perhaps brachiopods, they are not members of the Mollusca (see Vinther and Nielsen 2005;Caron et al 2006;Butterfield 2006 for a sampling of both pro and con arguments).…”
mentioning
confidence: 99%
“…Significant extracellular secretion is indicated by the residual three-dimensionality of teeth [8]. As iterated by Caron et al [2,7], the mouthparts comprise symmetrical transverse rows of solid teeth that are distinct from, but embedded in, a radular membrane; the rows pass round the end of a supporting apparatus, are sloughed anteriorly and replaced from the posterior, and contain more teeth when they are larger. But where Caron et al identified two denticulate teeth per row [2,7], this study recognizes each 'denticle' as a separate articulating tooth.…”
Section: Discussion (A) Reconstructionmentioning
confidence: 99%
“…The soft-bodied organisms Odontogriphus omalus and Wiwaxia corrugata from the Middle Cambrian Burgess Shale (Series 3-505 Ma) seem to represent early members of this group [1,2]; if so, they provide our best constraint on the ancestral mollusc. However, it has been suggested that Wiwaxia is more closely related to the annelid worms [3][4][5], and that Odontogriphus could have diverged from a lineage ancestral to both the molluscs and the annelids [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is on the dual supposition of the similarities of the sclerite microstructure to annelidan chaetae (Butterfield, 1990; see also Conway Morris and Peel, 1995) and the inferred transformation of the scleritome into parapodial bundles capable of locomotion and defense (Conway Morris and Peel, 1995;Struck, 2011). Arguments, especially on the nature of the radula-like mouthConway Morris et al-Burgess Shale-type taxa parts (Smith, 2012) and similarities to Odontogriphus (Caron et al, 2006) on the other hand point to a molluscan affinity (see also Smith, 2014). By itself, W. herka can add nothing material to this discussion, but it is worth emphasizing that if the wiwaxiids belong to a stem-group identified as the halwaxiids (Conway Morris and Caron, 2007) then shoe-horning them into a given phylum may serve to obscure how crucial anatomical transitions were achieved among which end-results are the setae of annelids (and brachiopods) or radula of mollusks.…”
Section: Genus Wiwaxia Walcott 1911amentioning
confidence: 99%